Sources of information available to senior secondary school student on the nutritional practices adopted in Delta State, Nigeria - Oghenevwarhe Itagar; Juliana Ego Azonuche; Diana Oritsegbubemi Arubayi (Humanities Horizon, 2026)
Promoting healthy eating among youth is hindered by limited access to reliable dietary guidance, which often leads to poor nutritional practices and adverse long-term health outcomes among adolescents. This study adopted an ex-post facto, descriptive survey design in Delta State, Nigeria. Out of a population of 14,819 public senior secondary students across three senatorial zones, a sample of 390 students from 18 schools was selected using Slovin’s formula and multistage sampling. Data was collected via a validated, 4-point Likert scale questionnaire (Cronbach’s Alpha = 0.81) with a 100% retrieval rate. Analysis involved percentages, mean scores, standard deviations, and t-test statistics using SPSS version 22. Based on 390 respondents, senior secondary students agreed that television (M = 3.47), friends/classmates (M = 3.26), radio (M = 2.90), and social media (M = 2.76) are available nutritional information sources, exceeding the 2.50 cut-off. Conversely, they disagreed on home economics textbooks, newspapers, and fiction books (M = 2.23 – 2.40). Standard deviations ranged from 0.63 to 0.99. Hypothesis testing revealed a significant locational difference in information sources between urban (N = 219, M = 21.42, SD = 2.62) and rural (N = 171, M = 12.35, SD = 2.38) students. With t-cal = 35.32 and p = 0.00 (at alpha = 0.05), the null hypothesis was rejected. In conclusion, secondary students rely heavily on electronic and social media for nutritional knowledge, while print media remains ineffective. Significant urban-rural disparities highlight the urgent need for equitable, localized nutritional interventions.